Mekanisme Penyelesaian Sengketa Penyedia Jasa Website Download Film Gratis Bagi Pencipta Film di Indonesia - Yonatan Andreas Putera; Hendra Djaja; I Gusti Ngurah Adyana; Ariyanti Ariyanti (University of Merdeka Malang, 2020)
Copyright infringement can have a negative impact on film makers both materially and morally. Coupled with the development of the internet, copyright infringement is not only realized in the form of pieces of VCD / DVD, but has penetrated into the internet media, namely the emergence of many websites or sites that provide free movie download services. The creators of these films and websites do not have a definite legal relationship. The emergence of these websites is of course very detrimental to the film creator because these websites operate illegally without any relationship agreement or agreement from the film creator and for the personal benefit of the website owner without thinking about the losses experienced by the film creator. But the creator can also report these websites if they feel aggrieved and of course if it is indeed proven to be carrying out illegal activities against the copyrighted films of the creator of the film. If it is proven to have committed an unlawful act, the website owner may be subject to sanctions in the form of prison or other compensation such as compensation for royalties. This research uses normative legal research with the aim of discussing how the dispute resolution mechanism between film creators and film website service providers.